Zoo Stories: Review of John Bierlein and the Staff of HistoryLink, Woodland: The Story of the Animals and People of Woodland Park Zoo & Andrew Flack, The Wild Within: Histories of a Landmark British Zoo - Rothfels, Nigel (Humanimalia, 2020)
John Bierlein and the Staff of HistoryLink, Woodland: The Story of the Animals and People of Woodland Park Zoo. Seattle: HistoryLink, 2017. 200pp. $29.95 pb.Andrew Flack, The Wild Within: Histories of a Landmark British Zoo. Charlottesville: University of Virginia Press, 2018. 272 pp. $39.50 hc; $39.50 e-book.